Online Purchasing Decisions through Brand Image based on Advertising Effectiveness with Epic model studies on traveloka.Com consumers - Sari, Ratna; Sulistina, Sulistina; Santi, Santi (Fakultas Ekonomi dan Bisnis Islam, 2023)
This study examines online stores (E-Commerce), especially online travel and refers to online purchasing decisions on brand image based on advertising effectiveness. One of online is PT Trinusa Travelindo or Traveloka,whichi sengaged in fields that require online and Traveloka.com has the innovation toticket buying and selling services onlinethat focus on online.The Epic Model is themost accurate method for measuring the effectiveness of advertisements that have been served in the community compared to themeasurement modelusing the Customer Response Index (CRI) and Direct Rating Method (DRM). This study aims to analyze and determine online purchasing decisions through brand image based on the effectiveness of advertising with the epicmodel study on Traveloka.com consumers. The method used in this research is quantitative with descriptiveand causal approach. To obtain data, the researcher used a questionnaire as an instrument to collect data and distributed it torespondentsonline. Datawascheckedusing smart PLS3.2.9.There sultsof hypothesis testing that have been carried out show that:1)advertising effectivenessis significantan dhasa positive effect on advertising effectiveness, 2) brand image is significant and has a positive effect on purchasing decisions. 3) the effectiveness of advertising is significant and has a positive effect on purchasing decisions